2020
DOI: 10.21203/rs.3.rs-50501/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitigating Arrhythmia Risk in Hydroxychloroquine and Azithromycin Treated COVID-19 Patients using Arrhythmia Risk Management Plan

Abstract: Background: Hydroxychloroquine and Azithromycin use is associated with QT interval prolongation and arrhythmias. Despite ongoing multiple clinical trials for treatment of COVID19 infection, no definite cardiac safety protocols were proposed. The aim of our study was to assess cardiac safety in COVID-19 patients treated with the combination of Hydroxychloroquine and Azithromycin using close monitoring and arrhythmia risk management plan.Methods and results: We retrospectively examined arrhythmia safety of treat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Clinical implications of the QT-prolongation, however, have conflicting data. Several studies have shown no significant difference in arrhythmogenic events and overall outcomes 92 , 93 , 94 . QTc prolongation tended to occur more often in COVID patients who had worsening renal disease and myocardial injury 95 .…”
Section: Cardiovascular Effects From Treatment/prevention Modalitiesmentioning
confidence: 99%
“…Clinical implications of the QT-prolongation, however, have conflicting data. Several studies have shown no significant difference in arrhythmogenic events and overall outcomes 92 , 93 , 94 . QTc prolongation tended to occur more often in COVID patients who had worsening renal disease and myocardial injury 95 .…”
Section: Cardiovascular Effects From Treatment/prevention Modalitiesmentioning
confidence: 99%
“…There is a risk of QT interval prolongation and arrhythmia associated with the experimental use of chloroquine/hydroxychloroquine for the treatment of COVID-19 infection, or prophylaxis. However, Maneikis, et al concluded that it would be possible to mitigate the risk of arrhythmia by utilizing an arrhythmia risk management plan ( 51 ).…”
Section: Covid-19 Effects On the Cardiovascular System And Correspondmentioning
confidence: 99%
“…32,49 A study retrospectively reviewed 81 patients treated with hydroxychloroquine and azithromycin and found that 7/81 (8.6%) had QTc prolongation (≥500 ms), with no patients developing ventricular tachycardia. 50 Therefore, the AIFA, EMA, U.S. Food and Drug Administration (FDA), and WHO do not recommend azithromycin or macrolide antibiotics for the treatment of COVID-19 without an underlying bacterial infection. 32…”
Section: Azithromycinmentioning
confidence: 99%